PENGEMBANGAN MEDIA AUDIO PODCAST DALAM MEMPELAJARI BENTUK KALIMAT BAHASA INGGRIS BAGI MAHASISWA TUNANETRA - Manaf, Yozi Gusrinaldi; Marlina, Marlina (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to develop an audio podcast-based learning media called "Podlish" to help visually impaired students understand sentence structures in English. The development followed the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. In the analysis phase, interviews with visually impaired students revealed their difficulties in understanding English materials that are often visual and not aligned with their auditory learning style. They expressed the need for simple explanations, clear narration, and accessible sentence examples. Based on these needs, the “Podlish” podcast was created, featuring theoretical explanations, sentence examples, and practice exercises—all in audio format. The narration is delivered in a clear voice and supported by non-distracting background music. Expert validation showed the media was highly appropriate with an average score of 84.2%, while practical testing with visually impaired students resulted in an 89.3% average score for usability. Revisions were made based on expert feedback, including improving audio quality, adding transcripts, and expanding accessibility. In conclusion, "Podlish" is an effective, practical, and inclusive learning tool.